(Un)Marked Language Use. A New Paradigm? Thoughts on the Variability of Conformity to Norms - Crudu, Mihai (Universitatea Transilvania Brasov, 2024)
The starting point of this article is the observation that certain grammatical aspects, especially endings, which are normally expected in language use, are sometimes not marked and therefore omitted in exceptional cases. An illustrative example would be the following pair: "Dem Biologen Müller fällt auf, dass ..." vs. "Biologe Müller fällt auf, dass ...." In the first case, the weak declension is marked because the definite article is also present, while in the second case, the noun remains uninflected, i.e., unmarked, due to the omission of the article. This essay explores this issue exemplarily, examining the conditions under which non-marking or non-adherence to a grammatical rule appears and whether there might be a pattern.
Keywords: (Non-)Marking; Language Usage; Grammatical Rule; Usage; Norm Compliance